Answer:
Step-by-step explanation:
Formula for circumference:
The radius given:
The circumference is:
Answer:
dude you rock
Step-by-step explanation:
2 ÷ p
B.
p + 2
C.
2 × p
D.
p – 2
Answer:
n<4
Step-by-step explanation:
Answer:
Step-by-step explanation:
Answer:
11/-30 Hope this helped :)
Step-by-step explanation:
15x + 4 = -1 1/2
15x = -5 1/2
x = 11/-2*1/15
x = - 11/-30
i will give a thanks if you reply with an answer! :)
Answer:
f(x) + g(x) = -9x³ - 14x² + 2x + 7
Step-by-step explanation:
This notation (f + g)(x) just wants you to add the two functions; it's the same thing as writing f(x) + g(x).
f(x) = -6x² + 9x + 7
g(x) = -9x³ - 8x² - 7x
All you have to do now is combine like terms and simplify.
f(x) + g(x) = (-6x² + 9x + 7) + (-9x³ - 8x² - 7x)
f(x) + g(x) = -6x² + 9x + 7 + -9x³ - 8x² - 7x
f(x) + g(x) = -9x³ - 8x² - 6x² + 9x - 7x + 7
f(x) + g(x) = -9x³ - 14x² + 2x + 7